2019
DOI: 10.1038/s41467-019-12641-4
|View full text |Cite
|
Sign up to set email alerts
|

HCMV-encoded US7 and US8 act as antagonists of innate immunity by distinctively targeting TLR-signaling pathways

Abstract: The mechanisms by which many human cytomegalovirus (HCMV)-encoded proteins help the virus to evade immune surveillance remain poorly understood. In particular, it is unknown whether HCMV proteins arrest Toll-like receptor (TLR) signaling pathways required for antiviral defense. Here, we report that US7 and US8 as key suppressors that bind both TLR3 and TLR4, facilitating their destabilization by distinct mechanisms. US7 exploits the ER-associated degradation components Derlin-1 and Sec61, promoting ubiquitinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Heat shock protein 27 (HSP27) has been identified as a regulator in facilitating endocytosis, ubiquitination, and degradation of TLR4 (Li et al, 2019). US7 and US8, which are encoded by human cytomegalovirus (HCMV), contribute to ubiquitination-mediated degradation of TLR3 and TLR4 (Park et al, 2019). Also, the ubiquitin E3 ligase Triad3A is previously demonstrated to promote TLR4 and TLR9 ubiquitination and degradation (Chuang and Ulevitch, 2004;Lu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock protein 27 (HSP27) has been identified as a regulator in facilitating endocytosis, ubiquitination, and degradation of TLR4 (Li et al, 2019). US7 and US8, which are encoded by human cytomegalovirus (HCMV), contribute to ubiquitination-mediated degradation of TLR3 and TLR4 (Park et al, 2019). Also, the ubiquitin E3 ligase Triad3A is previously demonstrated to promote TLR4 and TLR9 ubiquitination and degradation (Chuang and Ulevitch, 2004;Lu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SNAP23 and CDC42 are components of the secretory pathway and may affect levels of circulating cytokines [ 17 ]. US7 promotes the degradation of toll-like receptors (TLR) 3 and 4 via ubiquitin-dependent pathways [ 23 ]. TLR3 detects dsRNA, which is generated by both RNA and DNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The IE1 and IE2 proteins, which are synthesized after HCMV infection, can inhibit the IFN signal transduction and thereby inhibit the innate immune response (Paulus and Nevels, 2009). In addition, it has been suggested that US10 attenuates IFN-β (Park et al, 2019). The inhibition of cGAS activation and MITA trafficking by UL42 is contributes to the evasion of immune antiviral immunity by HCMV (Fu et al, 2019).…”
Section: Innate Responsementioning
confidence: 99%